Lithium iron phosphate particles, preparation method thereof, positive pole piece, secondary battery and power utilization device
By preparing large-particle lithium iron phosphate salt particles and doping modified elements to form a uniform and dense carbon cladding layer, the poor conductivity of lithium iron phosphate materials and processing difficulties caused by nanoification are solved, and the kinetic performance and the volume energy density of the battery are improved.
Patent Information
- Application Number
- CN202410027073.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-01-08
AI Technical Summary
The existing lithium iron phosphate materials have poor electronic conductivity, especially poor performance at low temperatures and large-magnifications, and nano-treatment leads to processing difficulties and material stability problems.
Large-particle lithium iron phosphate particles are prepared, with a particle size of 500 nm to 3000 nm, a BET specific surface area of 3m2/g to 8m2/g, and a carbon content of 0.8% to 2.0%. By doping elements such as Ti, V, Mg, and Nb, a uniform and dense carbon coating layer is formed to improve the dynamic performance of the particles.
The dynamic performance and volume energy density of lithium iron phosphate particles are improved, the processing difficulties caused by nanoification are solved, and the conductive and ion transport capabilities of the particles are enhanced.
Smart Images

Figure CN119852393A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium iron phosphate salt particle and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has rapidly become a global research hotspot due to its abundant resources, low price, environmental friendliness, and stable voltage of two-phase reaction. The cation arrangement in lithium iron phosphate is different from that in layered ternary materials and spinel LiMn2O4. 2+ At the 4c position of the oxygen octahedron, Li + It is located at the 4a position of the oxygen octahedron. The polyanion structure is stable, has a high thermal decomposition temperature, and has good thermal stability, but the octahedral structure of FeO6 is separated by the O atoms in the tetrahedral structure and is blocked by the phosphorus oxygen tetrahedron, and fails to form a continuous FeO6 network, resulting in poor electronic conductivity of lithium iron phosphate.
[0003] The industry usually uses doping, coating and particle nano-sizing to improve the conductivity of lithium iron phosphate. At low temperatures and high rates, the problems of electronic and ionic conductivity will become more prominent, and the material must be fully nano-sized. However, nano-sized materials have a higher specific surface energy, which will bring a series of processing problems, such as gel, fast water absorption, difficulty in drying, and low solid content of coating slurry. How to increase the particle size and reduce BET, thereby reducing the specific surface energy of the material while ensuring the kinetic performance, is a very meaningful engineering and technological advancement. Summary of the invention
[0004] The present application is made in view of the above-mentioned subject, and its purpose is to provide a lithium iron phosphate salt particle and its preparation method, a positive electrode plate, a secondary battery and an electrical device. The lithium iron phosphate salt particle has a large particle size and also has excellent kinetic properties when used as a positive electrode material.
[0005] The first aspect of the present application provides a lithium iron phosphate salt particle, wherein the primary average particle size of the lithium iron phosphate salt particle is 500nm to 3000nm, optionally 650nm to 2500nm, and the BET specific surface area is 3m 2 / g~8m 2 / g, optional 4m 2 / g~7m 2 / g, calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is Cx weight %, wherein 0.8≤Cx≤2.0, optionally 1.0≤Cx≤1.6, and further optionally, the ratio z of the BET specific surface area to Cx satisfies 1.5≤z≤8.5, optionally 3≤z≤6.
[0006] By making the primary average particle size of the lithium iron phosphate particles of the embodiment of the present application 500nm to 3000nm and the BET specific surface area 3m 2 / g~8m 2 / g, the carbon content calculated based on the total weight of the lithium iron phosphate salt particles is Cx weight % (0.8≤Cx≤2.0), and further optionally, the ratio z of the BET specific surface area of the lithium iron phosphate salt particles to Cx satisfies the range of 1.5≤z≤8.5, which can improve the dynamic properties of the lithium iron phosphate salt particles with an average particle size within the above range; the particles are kept in a suitable micron size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles, and the particles will not be limited to a large size and thus reduce the dynamic properties; in addition, it is beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery cell, and then increasing the volume energy density of the battery; in addition, it can avoid affecting the normal deintercalation of lithium ions due to excessive carbon coating density, thereby affecting the performance of the battery cell capacity.
[0007] Compared with the prior art, the lithium iron phosphate salt particles in the embodiment of the present application have a smaller specific surface area when containing the same carbon content, which means that the particles contain less floating carbon, which can make the carbon contained in the lithium iron phosphate salt particles more uniform and dense and each particle is coated, thereby improving the surface conductivity of the particles and improving their kinetic performance as a positive electrode material.
[0008] In any embodiment, the lithium iron phosphate salt has a molecular formula Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, Si, N, S, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.1.
[0009] By making the lithium iron phosphate salt of the embodiment of the present application have the above molecular formula and doping it with one or more of the above elements, a high-load bulk modification of the lithium iron phosphate salt particles is achieved, which helps to improve the bulk ion transport capacity of the lithium iron phosphate salt particles and can effectively solve the problem of poor kinetic performance inherent in large particles. In addition, by performing the doping, the lithium iron phosphate salt particles can show good kinetic performance when used as a positive electrode material. In the present application, the modification can be specifically manifested as doping and / or coating.
[0010] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb, and can be Ti. The content of Ti, V, Mg, and / or Nb is 1000ppm-10000ppm, and can be 2500ppm-6000ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0011] By doping the lithium iron phosphate salt of the embodiment of the present application with one or more of the above elements and making the content thereof within the above range, it is possible to better achieve metal bulk modification of the lithium iron phosphate salt particles while improving the primary average particle size of the lithium iron phosphate salt particles, further enhance the bulk ion transport capacity of the lithium iron phosphate salt particles, and better solve the problem of poor kinetic properties inherent in large particles.
[0012] In any embodiment, the lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles. Optionally, based on the total number of lithium iron phosphate salt particles, the number of single crystal particles accounts for more than 90%.
[0013] In the lithium iron phosphate particles of the embodiment of the present application, the carbon may exist in a state of being mixed with the lithium iron phosphate particles or in a state of being coated on the lithium iron phosphate particles. The carbon in the lithium iron phosphate particles may be coated on the lithium iron phosphate particles, thereby enabling the carbon to form a uniform and dense carbon coating layer on the surface of the lithium iron phosphate particles, thereby improving the conductivity of the particle surface.
[0014] In any embodiment, the capacity proportion of the lithium iron phosphate salt particles η≥88%, and the definition of η is: a battery having the lithium iron phosphate salt particles as the positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value at the discharge voltage of 3.2V is extracted as C1, and the capacity value at the discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
[0015] η represents the platform retention performance of the material, and this value is strongly correlated with the discharge power performance of the battery. When this value is large, the battery can still maintain good power performance when it is discharged to a low SOC (battery state of charge), that is, the voltage drop of the battery is small when the battery is discharged at a high current at low power. The capacity proportion η of the lithium iron phosphate salt particles of the embodiment of the present application is ≥88%, indicating that the lithium iron phosphate salt particles of the present application can enable the secondary battery to show good kinetic performance when used as a positive electrode material.
[0016] In any embodiment, the lithium iron phosphate salt particles satisfy at least one of a) to f):
[0017] a) the Dv10 of the lithium iron phosphate particles is ≥ 0.2 μm;
[0018] b) the Dv50 of the lithium iron phosphate particles is 0.5-5 μm;
[0019] c) the Dv90 of the lithium iron phosphate salt particles is ≤10 μm;
[0020] d) the Dv99 of the lithium iron phosphate particles is ≤12 μm;
[0021] e) The powder compaction density of the lithium iron phosphate salt under a pressure of 3T is ≥2.25g / cm 3 ;
[0022] f) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
[0023] In this application, the above Dv10, Dv90, and Dv99 refer to the particle sizes corresponding to the volume cumulative particle size distribution percentages in the particles reaching 10%, 90%, and 99%, respectively. The test method is the same as that of the above Dv50, and the standard in the examples of this application can be used for determination.
[0024] It should be noted that the Dv10 is a large index, so no upper limit can be given, and the Dv90 is a small index, so no lower limit can be given.
[0025] By making the lithium iron phosphate salt particles satisfy at least one of a) to f), the lithium iron phosphate salt particles can achieve the above technical effects better.
[0026] In the present application, the test method of the powder resistivity is: refer to the national standard GB / T33822-2017, use a powder resistivity meter (Suzhou Jinglattice, ST2722 model), weigh 1g of sample (the error is within ±0.005g), add it to the feeding chamber, apply a pressure of 8MPa, test the forward resistivity and reverse resistivity of the sample respectively, and take the average of the two as the powder resistivity of the sample.
[0027] In this application, the compacted density of the powder is defined as: during the external force compression process, as the powder moves and deforms, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced, thus forming a compact with a certain density and strength, the unit is g / cm 3 .
[0028] The compaction density test method is as follows: referring to the national standard GB / T 24533-2009, a certain amount of powder is placed on a compaction mold, and a metal disc is placed on the upper and lower parts of the mold. The powder is placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on a compaction density instrument. Different pressures are set, and the thickness of the powder under different pressures can be read on the device. The compaction density is calculated by ρ=m / v.
[0029] According to the following powder compaction density calculation results, ρc=m / V=m / (S×H); where ρc is the powder compaction density (g / cm 3 ), m is the mass of the material (g), S is the bottom area of the mold (1.327cm 2 ), H is the height of the sample after compaction (cm).
[0030] The second aspect of the present application provides a method for preparing lithium iron phosphate salt particles, comprising: providing a raw material containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sinterings, wherein the temperature of the first sintering is 500°C-760°C, optionally 550°C-720°C, and the carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%; the temperature of the second sintering is 700°C-800°C, optionally 720°C-780°C, and the carbon content of the material after the second sintering is 0.8 wt%-2.0 wt%, optionally 1.0 wt%-1.6 wt%.
[0031] In the preparation method of the lithium iron phosphate salt particles of the embodiment of the present application, two sinterings are implemented. Among them, by controlling the temperature of the first sintering within the above range and making the carbon content of the intermediate after sintering within the above range, the lithium iron phosphate precursor obtained after the first sintering can have a larger particle size, which directly improves the powder compaction of the final product and the compaction density of the pole piece. In addition, by adding a lower content of carbon source during the first sintering, the barrier effect of the carbon layer on the growth process of the lithium iron phosphate particles is greatly reduced, which is conducive to the crystal growth of the particles at a lower temperature, and is also conducive to the solid-phase diffusion reaction between the modifier and the lithium iron phosphate material, thereby achieving a higher concentration of metal ion modification. Compared with the traditional method of using high temperature to achieve particle growth, the above-mentioned preparation method of the present application can first synthesize large particles at a lower temperature, which can improve the phenomenon of cracking of the carbon layer on the surface of the particles at high temperature and improve the density of the surface carbon; at the same time, during the first sintering process, the carbon source can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product; by controlling the temperature of the second sintering within the above-mentioned range and making the carbon content of the sintered material 0.8 wt%-2.0 wt%, carbon can be coated on the surface of the lithium iron phosphate salt particles to form a lithium iron phosphate material with a uniform and dense carbon coating layer on which each particle is coated, thereby greatly improving the conductivity of the particle surface.
[0032] In any embodiment, the lithium iron phosphate salt particles contain at least one of Ti, V, Mg, and / or Nb elements, and the content of the element is 1000ppm-10000ppm, optionally 2500ppm-6000ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0033] In some embodiments, the content of the element may be 2500 ppm-6000 ppm. Specific options include 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3400ppm, 3500ppm, 3600ppm, 3700ppm, 3800ppm, 3900ppm, 4000ppm, 4100ppm, 4200ppm, 4300ppm, 4400ppm, 4500ppm, 4600ppm, 4700ppm, 4800ppm, 4900ppm, 5000ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 5500ppm, 5600ppm, 5700ppm, 5800ppm, 5900ppm or 6000ppm, or the range between any two of the above values.
[0034] By doping the lithium iron phosphate salt of the embodiment of the present application with one or more of the above elements and making the content thereof within the above range, it is possible to better achieve metal bulk modification of the lithium iron phosphate salt particles while improving the primary average particle size of the lithium iron phosphate salt particles, further enhance the bulk ion transport capacity of the lithium iron phosphate salt particles, and better solve the problem of poor kinetic properties inherent in large particles.
[0035] In any embodiment, in the preparation method of the lithium iron phosphate salt particles, a first crushing is performed after the first sintering, and a second crushing is performed after the second sintering, wherein the Dv50 of the product after the first crushing is 300nm-1200nm, and can be optionally 400nm-1100nm; the Dv50 of the product after the second crushing is 500nm-5000nm, and can be optionally 300nm-2500nm.
[0036] In the preparation method of the lithium iron phosphate salt particles of the embodiment of the present application, crushing after two sinterings is implemented. By performing the first crushing after the first sintering, the Dv50 of the product is 300nm-1200nm, which can avoid the growth barrier of the crystal by the carbon material and the modifying element, and obtain a micron-level lithium iron phosphate precursor; by performing the second crushing after the second sintering, the Dv50 of the product is 500nm-3000nm, and lithium iron phosphate salt particles with a desired particle size can be obtained, and a uniform and dense carbon coating layer is obtained in which each particle is coated, which greatly improves the surface conductivity of the particles.
[0037] In any embodiment, the preparation method of the lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, wherein the mixing ratio of the lithium source, the iron source, and the phosphorus source, calculated on the basis of the atomic molar number of each element, satisfies Fe:P=0.96-0.985, Li:Fe=1.0-1.1:0.95-1.1; the carbon source and the carbon film-forming agent, calculated on the basis of the weight ratio, satisfy the carbon source:carbon film-forming agent=9:1-2:8.
[0038] By using raw materials containing a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent in the above-mentioned proportions, it is possible to achieve good modification, and to form the obtained lithium iron phosphate salt particle precursor into larger particles, thereby being able to well form the primary average particle size, carbon content, BET specific surface area, and z value of the lithium iron phosphate salt particles of the first aspect of this application. Specifically, as described above, by making the primary average particle size of the lithium iron phosphate salt particles of the embodiment of the present application 500nm to 3000nm, the particles can be kept at a suitable micron-level size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles (in this field, it is difficult to process nano-sized particles), and the particles will not be limited by the excessive size and the kinetic performance will be reduced. In addition, by making the BET specific surface area of the lithium iron phosphate salt particles of the embodiment of the present application 3m 2 / g~8m 2 / g, which can be beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery core, and then increasing the volume energy density of the battery. Further optionally, by making the ratio z of the BET specific surface area of the lithium iron phosphate salt particles of the embodiment of the present application to Cx satisfy the range of 1.5≤z≤8.5, the carbon contained in the lithium iron phosphate salt particles can be made more uniform and dense and each particle is coated, thereby improving the surface conductivity of the particles.
[0039] In any embodiment, in the preparation method of the lithium iron phosphate salt particles, the lithium source is a lithium compound, including one or more of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide and lithium acetate, and lithium carbonate can be selected; the iron source is an iron compound, including ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric hydroxide, and ferric oxide can be selected; the phosphorus source is a phosphoric acid compound, including phosphoric acid, dihydrogen phosphate, The present invention relates to a novel carbon-containing material comprising one or more of ammonium and diammonium hydrogen phosphate, which can be phosphoric acid; the modifier comprises at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethanol, niobium oxalate, niobium pentoxide, magnesium hydroxide and magnesium nitrate, which can be titanium dioxide; the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose and lactose, which can be glucose; the carbon film-forming agent comprises one or more of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone and polyvinyl alcohol, which can be polyaniline.
[0040] By selecting the above substances as the lithium source, iron source, phosphorus source, modifier, carbon source and carbon film-forming agent respectively used in the preparation method of the lithium iron phosphate salt particles of the embodiment of the present application, the primary average particle size, carbon content, BET specific surface area and z value of the lithium iron phosphate salt particles of the first aspect of the present application can be well formed. Thereby, the large particle size of the lithium iron phosphate salt particles of the embodiment of the present application is better achieved, and at the same time, excellent kinetic performance is achieved when it is used as a positive electrode material.
[0041] In any embodiment, the heating rates in the first sintering and the second sintering are independently 2°C / min-20°C / min, the constant temperature time of the first sintering is 1h-6h; and the constant temperature time of the second sintering is 2h-12h.
[0042] By independently controlling the heating rate and the constant temperature time in the first sintering and the second sintering within the above range, it is possible to prevent excessive side reactions during the sintering process due to too fast a heating rate, thereby affecting the primary average particle size, carbon content, BET specific surface area and z value of the obtained lithium iron phosphate salt particles. In this way, the large particle size of the lithium iron phosphate salt particles of the embodiment of the present application is better achieved, and excellent kinetic performance is achieved when it is used as a positive electrode material.
[0043] In any embodiment, after the first sintering and before the second sintering, the product after the first sintering is carbon-coated, and the amount of the carbon coating is 0.01 wt%-1.99 wt%, optionally 0.2 wt%-1.6 wt%, based on the total weight of the product after the first sintering.
[0044] By coating the product after the first sintering with carbon within the above-mentioned content range after the first sintering and before the second sintering, a uniform and dense carbon coating layer can be formed on the surface of the lithium iron phosphate salt particles during the second sintering process, and each particle is coated.
[0045] In any embodiment, the carbon coating is performed by vapor deposition during sintering, or by carbonizing and coating the carbon source at high temperature.
[0046] In the preparation method of the lithium iron phosphate salt particles of the embodiment of the present invention, the implementation method of the carbon coating is not particularly limited, and the lithium iron phosphate salt particles can be optionally carbon-coated by a vapor deposition method, thereby forming a uniform and dense carbon coating layer on the surface of the lithium iron phosphate salt particles and coating each particle.
[0047] In any embodiment, after the first sintering and the second sintering, the sintered product is crushed, and the crushing can be selected from one or more of grinding, sand milling, mechanical crushing, and air flow crushing.
[0048] In the method for preparing the lithium iron phosphate salt particles according to the embodiment of the present invention, the pulverization method is not particularly limited. By adopting the above-mentioned specific pulverization method, it is advantageous to obtain the desired primary average particle size.
[0049] The third aspect of the present application provides a positive electrode plate, which comprises the lithium iron phosphate salt particles of the first aspect of the present application as a positive electrode material.
[0050] The fourth aspect of the present application provides a secondary battery, which includes the positive electrode sheet of the third aspect of the present application.
[0051] A fifth aspect of the present application provides an electrical device, which includes the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 are SEM and TEM images of lithium iron phosphate particles according to an embodiment of the present application, wherein: Figure 1 a corresponds to an image of lithium iron phosphate particles observed under a SEM (scanning electron microscope) according to an embodiment of the present application; Figure 1 b and Figure 1 c corresponds to the image of the lithium iron phosphate salt particles according to one embodiment of the present application observed under a TEM (transmission electron microscope).
[0053] Figure 2 is a SEM image of an embodiment of the present application and existing lithium iron phosphate particles, wherein: Figure 2 a is a SEM image of Example 10; Figure 2 b is a SEM image of existing lithium iron phosphate salt particles.
[0054] Figure 3 It is a schematic diagram exemplarily showing the particle size of the primary particles of the present application.
[0055] Figure 4 This is a capacity performance diagram of the lithium iron phosphate salt particles according to one embodiment of the present application at 0.1C and 1C rates.
[0056] Figure 5 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0057] Figure 6 yes Figure 5 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0058] Figure 7 is a schematic diagram of a battery module according to an embodiment of the present application.
[0059] Figure 8 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0060] Fig. 9 yes Figure 8 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0061] Fig.10 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0062] Description of reference numerals:
[0063] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0064] The following is a detailed description of the lithium iron phosphate salt particles and their preparation methods, positive electrode plates, secondary batteries and electrical devices of the present application. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0065] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0066] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0068] If not otherwise specified, all steps of the present application may be performed sequentially or randomly, and may be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0069] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0070] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0071] As the positive electrode material of secondary batteries, lithium iron phosphate has the problem of poor conductivity. To address this, the industry usually uses methods such as doping, coating and particle nano-crystallization to improve the conductivity of lithium iron phosphate.
[0072] The carbon coating and nano-sizing methods commonly used in the industry at present reduce the primary average particle size while introducing a loose carbon layer, which will significantly increase the specific surface area of the material, causing a series of processing and manufacturing problems during the processing and use of the material, increasing the production and manufacturing costs and reducing the production rate. For example, slurry gel, cracking of the pole piece coating, water absorption of the powder exposed to the air, powder loss in the membrane area of the pole piece during the slitting process, and small particles falling off during the cold pressing process. This series of processing problems may affect the life of the battery.
[0073] Therefore, preparing large-particle lithium iron phosphate positive electrode materials and improving the material's kinetic properties are of great significance for industrialization. This is described in detail below.
[0074] [Lithium iron phosphate particles]
[0075] The primary average particle size of the lithium iron phosphate particles in the embodiment of the present application is 500nm to 3000nm, and can be 650nm to 2500nm, and the BET specific surface area is 3m 2 / g~8m 2 / g, optional 4m 2 / g~7m 2 / g, calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is Cx weight %, wherein 0.8≤Cx≤2.0, and optionally 1.0≤Cx≤1.6.
[0076] In some embodiments, the primary average particle size of the lithium iron phosphate particles may be 500nm, 600nm, 650nm, 700nm, 790nm, 800nm, 870nm, 900nm, 920nm, 1000nm, 1100nm, 1200nm, 1250nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm, 2100nm, 2200nm, 2300nm, 2400nm, 2500nm, 2600nm, 2700nm, 2800nm, 2900nm or 3000nm, or a range between any two of the above values. In some embodiments, the BET specific surface area of the lithium iron phosphate particles may be 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 7.2m 2 / g, 7.8m 2 / g or 8m 2 / g, or the range between any two of the above values. In some embodiments, the carbon content of the lithium iron phosphate particles can be 0.8 wt%, 0.9 wt%, 0.94 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt% or 2.0 wt%, or the range between any two of the above values.
[0077] In this article, the term "primary average particle size" refers to the particle size value obtained by statistically analyzing the particle size of particles using the long diameter statistical method under the field of view of a scanning electron microscope. In the particle size statistical process, particles with a primary average particle size less than or equal to 80nm are not included in the statistical range. The primary average particle size of this application is as follows Figure 3As shown. The primary average particle size refers to the average particle size of primary particles. In this article, "primary particles" refer to particles that do not have obvious agglomeration interfaces in the particle scanning electron microscope image, but may have tiny pores and point or line defects, which are different from powder particles that are the smallest units without structures such as stacking and flocculation. The determination method of the primary average particle size, carbon content and BET specific surface area can be carried out using the determination method described in the examples.
[0078] In the embodiment of the present application, the primary average particle size of the lithium iron phosphate particles is 500 nm to 3000 nm, and the BET specific surface area is 3 m 2 / g~8m 2 / g, the carbon content calculated based on the total weight of the lithium iron phosphate salt particles is Cx weight % (0.8≤Cx≤2.0), which can improve the dynamic properties of the lithium iron phosphate salt particles with an average particle size within the above range; the particles are kept in a suitable micron-level size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles, and the particles will not be limited by the excessive size and thus reduce the dynamic properties; in addition, it is beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery cell, and then increasing the volume energy density of the battery; in addition, it can avoid affecting the normal deintercalation of lithium ions due to the excessively high density of the carbon coating, thereby affecting the performance of the battery cell capacity.
[0079] Compared with the prior art, the lithium iron phosphate salt particles in the embodiment of the present application have a smaller specific surface area when containing the same carbon content, which means that the particles contain less floating carbon, which can make the carbon contained in the lithium iron phosphate salt particles more uniform and dense and each particle is coated, thereby improving the surface conductivity of the particles and improving their kinetic performance as a positive electrode material.
[0080] In any embodiment, the ratio z of the BET specific surface area to Cx satisfies 1.5≤z≤8.5, and can optionally satisfy 3≤z≤6.
[0081] In some embodiments, the ratio z of the BET specific surface area to Cx may be 1.5, 2.0, 2.5, 3.0, 3.9, 3.5, 3.75, 4.0, 4.17, 4.5, 5.0, 5.5, 5.71, 5.83, 6.0, 6.5, 7.0, 7.5, 8.0 or 8.5, or a range between any two of the above values.
[0082] By further limiting the ratio z to satisfy the above range, it can be intuitively reflected that the lithium iron phosphate salt particles in the embodiment of the present application contain less floating carbon, and the carbon coating is more uniform and dense, thereby further improving its conductivity and kinetic performance as a positive electrode material.
[0083] In any embodiment, the lithium iron phosphate salt has a molecular formula Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, Si, N, S, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.1.
[0084] By making the lithium iron phosphate salt of the embodiment of the present application have the above molecular formula and doping it with one or more of the above elements, a high-load bulk modification of the lithium iron phosphate salt particles is achieved, which helps to improve the bulk ion transport capacity of the lithium iron phosphate salt particles and can effectively solve the problem of poor kinetic performance inherent in large particles. In addition, by performing the doping, the lithium iron phosphate salt particles can show good kinetic performance when used as a positive electrode material. In the present application, the modification can be specifically manifested as doping and / or coating.
[0085] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb, and can be Ti. Calculated based on the total weight of the lithium iron phosphate salt particles, the content of Ti, V, Mg and / or Nb is 1000ppm-10000ppm, and can be 2500ppm-6000ppm. Specific options include 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3400ppm, 3500ppm, 3600ppm, 3700ppm, 3800ppm, 3900ppm, 4000ppm, 4100ppm, 4200ppm, 4300ppm, 4400ppm, 4500ppm, 4600ppm, 4700ppm, 4800ppm, 4900ppm, 5000ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 5500ppm, 5600ppm, 5700ppm, 5800ppm, 5900ppm or 6000ppm, or the range between any two of the above values.
[0086] In some embodiments, the lithium iron phosphate salt has a molecular formula of Li m A a Fe x D d Py E e O z G g , wherein A includes at least one element selected from Al, Na, K or Mg; D includes at least one element selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti or V; E includes at least one element selected from B, S, Si or N; G includes at least one element selected from S, F, Cl or Br; m is selected from the range of 0.95 to 1.15; a is selected from the range of 0 to 0.1; x is selected from the range of 0.95 to 1; d is selected from the range of 0 to 0.1; y is selected from the range of 0.95 to 1; e is selected from the range of 0 to 0.1; z is selected from the range of 3.5 to 4; g is selected from the range of 0 to 0.1.
[0087] By doping the lithium iron phosphate salt of the embodiment of the present application with one or more of the above elements and making the content thereof within the above range, it is possible to better achieve metal bulk modification of the lithium iron phosphate salt particles while improving the primary average particle size of the lithium iron phosphate salt particles, further enhance the bulk ion transport capacity of the lithium iron phosphate salt particles, and better solve the problem of poor kinetic properties inherent in large particles.
[0088] In any embodiment, the lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles. Optionally, based on the total number of particles of the lithium iron phosphate salt particles, the number of single crystal particles accounts for more than 90%. A single crystal refers to a structurally complete crystal grown from a crystal nucleus, and there are no grain boundaries in the single crystal; a polycrystal is a crystal formed by a large number of small single crystal particles randomly oriented, and there are grain boundaries inside the polycrystal. Different from a perfect single crystal, the large single crystal mentioned in this article may have tiny defects, such as micropores inside, a small number of points and surfaces, or a small number of particles on the surface of a particle sticking to each other. However, the single crystal referred to in this article is a whole in the field of view of the TEM photo.
[0089] In an embodiment of the present application, based on the total number of lithium iron phosphate salt particles, the proportion of the single crystal particles is controlled within the above range. Compared with polycrystalline and secondary agglomerates, the proportion of single crystal particles is high, the barrier of grain boundaries to lithium ions is smaller, the transmission rate of lithium ions is faster, and the kinetic performance is better.
[0090] In the lithium iron phosphate particles of the embodiment of the present application, the carbon may exist in a state of being mixed with the lithium iron phosphate particles or in a state of being coated on the lithium iron phosphate particles. The carbon in the lithium iron phosphate particles may be coated on the lithium iron phosphate particles, thereby enabling the carbon to form a uniform and dense carbon coating layer on the surface of the lithium iron phosphate particles, thereby improving the conductivity of the particle surface.
[0091] In any embodiment, the capacity proportion of the lithium iron phosphate salt particles η≥88%, and the definition of η is: a battery having the lithium iron phosphate salt particles as the positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value at the discharge voltage of 3.2V is extracted as C1, and the capacity value at the discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
[0092] The η value can characterize the kinetic properties of the lithium iron phosphate particles, and can be adjusted by adjusting the primary average particle size of the particles, the carbon content, the ratio of the carbon source and the film-forming agent, the modifier and its content. The η represents the platform retention performance of the material, and this value is strongly correlated with the discharge power performance of the battery. When this value is large, the battery can still maintain good power performance when discharged to a low SOC (battery state of charge), that is, the voltage drop value of the battery is small when the battery is discharged at a high current at low power. The capacity proportion η of the lithium iron phosphate salt particles of the embodiment of the present application is ≥88%, indicating that the lithium iron phosphate salt particles of the present application can enable the secondary battery to show good kinetic properties when used as a positive electrode material.
[0093] In any embodiment, the lithium iron phosphate salt particles satisfy at least one of a) to f):
[0094] a) the Dv10 of the lithium iron phosphate particles is ≥ 0.2 μm;
[0095] b) the Dv50 of the lithium iron phosphate particles is 0.5 μm-5 μm;
[0096] c) the Dv90 of the lithium iron phosphate salt particles is ≤10 μm;
[0097] d) the Dv99 of the lithium iron phosphate particles is ≤12 μm;
[0098] e) The powder compaction density of the lithium iron phosphate salt under a pressure of 3T is ≥2.25g / cm 3 ;
[0099] f) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
[0100] In this application, the above Dv10, Dv90, and Dv99 refer to the particle sizes corresponding to the volume cumulative particle size distribution percentages in the particles reaching 10%, 90%, and 99%, respectively. The test method is the same as that of the above Dv50, and the standard in the examples of this application can be used for determination.
[0101] It should be noted that the Dv10 is a large index, so no upper limit can be given, and the Dv90 is a small index, so no lower limit can be given.
[0102] By making the lithium iron phosphate salt particles satisfy at least one of a) to f), the lithium iron phosphate salt particles can achieve the above technical effects better.
[0103] In the present application, the test methods of the above-mentioned Dv10, Dv90 and Dv99 are the same as those of the above-mentioned Dv50, and can be measured using the standards in the embodiments of the present application.
[0104] In the present application, the test method of the powder resistivity is: refer to the national standard GB / T33822-2017, use a powder resistivity meter (Suzhou Jinglattice, ST2722 model), weigh 1g of sample (the error is within ±0.005g), add it to the feeding chamber, apply a pressure of 8MPa, test the forward resistivity and reverse resistivity of the sample respectively, and take the average of the two as the powder resistivity of the sample.
[0105] In this application, the compacted density of the powder is defined as: during the external force compression process, as the powder moves and deforms, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced, thus forming a compact with a certain density and strength, the unit is g / cm 3 .
[0106] The compaction density test method is as follows: referring to the national standard GB / T 24533-2009, a certain amount of powder is placed on a special compaction mold (the mold diameter is known), and a metal disc is placed on the upper and lower parts of the hollow mold. The powder is placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on the compaction density instrument. Different pressures are set, and the thickness of the powder under different pressures can be read on the device. The compaction density is calculated by ρ=m / v.
[0107] According to the following powder compaction density calculation results, ρc=m / V=m / (S*H); where ρc is the powder compaction density (g / cm 3 ), m is the mass of the material (g), S is the bottom area of the mold (1.327cm 2), H is the height of the sample after compaction (cm).
[0108] [Preparation method of lithium iron phosphate particles]
[0109] The preparation method of the lithium iron phosphate salt particles of the embodiment of the present application can prepare the lithium iron phosphate salt particles of the present application. The preparation method of the lithium iron phosphate salt particles of the embodiment of the present application includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and sintering at least twice, wherein the temperature of the first sintering is 500°C-760°C, optionally 550°C-720°C, and the carbon content of the material after the first sintering is 0.01% by weight-0.79% by weight, optionally 0.05% by weight-0.4% by weight; the temperature of the second sintering is 700°C-800°C, optionally 720°C-780°C, and the carbon content of the material after the second sintering is 0.8% by weight-2.0% by weight, optionally 1.0% by weight-1.6% by weight.
[0110] In some embodiments, the temperature of the first sintering may be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 655°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C or 760°C, or a range between any two of the above values. The temperature of the second sintering may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 755°C, 760°C, 770°C, 780°C, 790°C or 800°C, or a range between any two of the above values. The carbon content of the material after the first sintering can be selected to be 0.01 weight%, 0.05 weight%, 0.10 weight%, 0.15 weight%, 0.2 weight%, 0.25 weight%, 0.3 weight%, 0.35 weight%, 0.4 weight%, 0.45 weight%, 0.5 weight%, 0.55 weight%, 0.6 weight%, 0.65 weight%, 0.7 weight%, 0.75 weight%, 0.79 weight%; the carbon content of the material after the second sintering is 0.8 weight%-2.0 weight%, which can be selected as 0.8 weight%, 0.9 weight%, 1 weight%, 1.1%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight% or 2.0 weight%, or a range between any two of the above values.
[0111] In the preparation method of the lithium iron phosphate salt particles of the embodiment of the present application, two sinterings are implemented. Among them, by controlling the temperature of the first sintering within the above range and making the carbon content of the intermediate after sintering within the above range, the lithium iron phosphate precursor obtained after the first sintering can have a larger particle size, which directly improves the powder compaction of the final product and the compaction density of the pole piece. In addition, by adding a lower content of carbon source during the first sintering, the barrier effect of the carbon layer on the growth process of the lithium iron phosphate particles is greatly reduced, which is conducive to the crystal growth of the particles at a lower temperature, and is also conducive to the solid-phase diffusion reaction between the modifier and the lithium iron phosphate material, thereby achieving a higher concentration of metal ion modification. Compared with the traditional method of using high temperature to achieve particle growth, the above-mentioned preparation method of the present application can first synthesize large particles at a lower temperature, which can improve the phenomenon of cracking of the carbon layer on the surface of the particles at high temperature and improve the density of the surface carbon; at the same time, during the first sintering process, the carbon source can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product; by controlling the temperature of the second sintering within the above-mentioned range and making the carbon content of the sintered material 0.8 wt%-2.0 wt%, carbon can be coated on the surface of the lithium iron phosphate salt particles to form a lithium iron phosphate material with a uniform and dense carbon coating layer on which each particle is coated, thereby greatly improving the conductivity of the particle surface.
[0112] In any embodiment, the lithium iron phosphate salt particles contain at least one of Ti, V, Mg, and / or Nb elements, and the content of the element is 1000ppm-10000ppm, optionally 2500ppm-6000ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0113] In some embodiments, the content of the element may be 2500 ppm-6000 ppm. Specific options include 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3400ppm, 3500ppm, 3600ppm, 3700ppm, 3800ppm, 3900ppm, 4000ppm, 4100ppm, 4200ppm, 4300ppm, 4400ppm, 4500ppm, 4600ppm, 4700ppm, 4800ppm, 4900ppm, 5000ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 5500ppm, 5600ppm, 5700ppm, 5800ppm, 5900ppm or 6000ppm, or the range between any two of the above values.
[0114] By doping the lithium iron phosphate salt of the embodiment of the present application with one or more of the above elements and making the content thereof within the above range, it is possible to better achieve metal bulk modification of the lithium iron phosphate salt particles while improving the primary average particle size of the lithium iron phosphate salt particles, further enhance the bulk ion transport capacity of the lithium iron phosphate salt particles, and better solve the problem of poor kinetic properties inherent in large particles.
[0115] In any embodiment, in the preparation method of the lithium iron phosphate salt particles, a first crushing is performed after the first sintering, and a second crushing is performed after the second sintering, wherein the Dv50 of the product after the first crushing is 300nm-1200nm, and can be optionally 400nm-1100nm; the Dv50 of the product after the second crushing is 500nm-5000nm, and can be optionally 300nm-2500nm.
[0116] In some embodiments, the Dv50 of the product after the first crushing is 300nm, 350nm, 400nm, 500nm, 550nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, or 1200nm, or a range between any two of the above values. In some embodiments, the Dv50 of the product after the second crushing is 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 3000nm, 3300nm, 3500nm, 3700nm, 4000nm, 4300nm, 4500nm, 4700nm, 5000nm, or a range between any two of the above values.
[0117] Herein, the term "Dv50" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 50%. The determination of Dv50 can be carried out using the determination method described in the examples.
[0118] In the preparation method of the lithium iron phosphate salt particles of the embodiment of the present application, crushing after two sinterings is implemented. By performing the first crushing after the first sintering, the Dv50 of the product is 300nm-1200nm, which can avoid the growth barrier of the crystal by the carbon material and the modifying element, and obtain a micron-level lithium iron phosphate precursor; by performing the second crushing after the second sintering, the Dv50 of the product is 500nm-3000nm, and lithium iron phosphate salt particles with a desired particle size can be obtained, and a uniform and dense carbon coating layer is obtained in which each particle is coated, which greatly improves the surface conductivity of the particles.
[0119] In any embodiment, the preparation method of the lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, wherein the mixing ratio of the lithium source, the iron source, and the phosphorus source, calculated on the basis of the atomic molar number of each element, satisfies Fe:P=0.96-0.985:1, Li:Fe=1.0-1.1:0.95-1.1; the carbon source and the carbon film-forming agent, calculated on the basis of the weight ratio, satisfy the carbon source:carbon film-forming agent=9:1-2:8.
[0120] In some embodiments, the mixing ratio of the iron source and the phosphorus source, calculated on the basis of the atomic moles of each element, satisfies Fe:P=0.96:1, Fe:P=0.965:1, Fe:P=0.97:1, Fe:P=0.975:1, Fe:P=0.98:1 or Fe:P=0.985:1.
[0121] In some embodiments, the mixing ratio of the lithium source to the iron source, calculated on the basis of the atomic moles of each element, satisfies Li:Fe=1.0:1.1, Li:Fe=0.99:1.1, Li:Fe=0.98:1.1, Li:Fe=0.97:1.1, Li:Fe=0.96:1.1 or Li:Fe=0.95:1.1.
[0122] In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent may be 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7 or 2:8.
[0123] By using raw materials containing a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent in the above-mentioned proportions, it is possible to achieve good modification, and to form the obtained lithium iron phosphate salt particle precursor into larger particles, thereby being able to well form the primary average particle size, carbon content, BET specific surface area, and z value of the lithium iron phosphate salt particles of the first aspect of this application. Specifically, as described above, by making the primary average particle size of the lithium iron phosphate salt particles of the embodiment of the present application 500nm to 3000nm, the particles can be kept at a suitable micron-level size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles (in this field, it is difficult to process nano-sized particles), and the particles will not be limited by the excessive size and the kinetic performance will be reduced. In addition, by making the BET specific surface area of the lithium iron phosphate salt particles of the embodiment of the present application 3m 2 / g~8m 2 / g, which can be beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery core, and then increasing the volume energy density of the battery. Further optionally, by making the ratio z of the BET specific surface area of the lithium iron phosphate salt particles of the embodiment of the present application to Cx satisfy the range of 1.5≤z≤8.5, the carbon contained in the lithium iron phosphate salt particles can be made more uniform and dense and each particle is coated, thereby improving the surface conductivity of the particles.
[0124] In any embodiment, in the preparation method of the lithium iron phosphate salt particles, the lithium source is a lithium compound, including one or more of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide and lithium acetate, and lithium carbonate can be selected; the iron source is an iron compound, including ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric hydroxide, and ferric oxide can be selected; the phosphorus source is a phosphoric acid compound, including phosphoric acid, dihydrogen phosphate, The present invention relates to a novel carbon-containing material comprising one or more of ammonium and diammonium hydrogen phosphate, which can be phosphoric acid; the modifier comprises at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethanol, niobium oxalate, niobium pentoxide, magnesium hydroxide and magnesium nitrate, which can be titanium dioxide; the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose and lactose, which can be glucose; the carbon film-forming agent comprises one or more of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone and polyvinyl alcohol, which can be polyaniline.
[0125] By selecting the above substances as the lithium source, iron source, phosphorus source, modifier, carbon source and carbon film-forming agent respectively used in the preparation method of the lithium iron phosphate salt particles of the embodiment of the present application, the primary average particle size, carbon content, BET specific surface area and z value of the lithium iron phosphate salt particles of the first aspect of the present application can be well formed. Thereby, the large particle size of the lithium iron phosphate salt particles of the embodiment of the present application is better achieved, and at the same time, excellent kinetic performance is achieved when it is used as a positive electrode material.
[0126] In any embodiment, the heating rates in the first sintering and the second sintering are independently 2°C / min-20°C / min, the constant temperature time of the first sintering is 1h-6h; and the constant temperature time of the second sintering is 2h-12h.
[0127] In some embodiments, the heating rates in the first sintering and the second sintering are each independently 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 17°C / min or 20°C / min.
[0128] In some embodiments, the constant temperature sintering time of the first sintering is 1-6 hours. In some embodiments, the constant temperature sintering time of the first sintering can be selected as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0129] In some embodiments, the constant temperature sintering time of the second sintering is 2-12 hours. In some embodiments, the constant temperature sintering time of the second sintering can be selected as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours.
[0130] By independently controlling the heating rate and the constant temperature time in the first sintering and the second sintering within the above range, it is possible to prevent excessive side reactions during the sintering process due to too fast a heating rate, thereby affecting the primary average particle size, carbon content, BET specific surface area and z value of the obtained lithium iron phosphate salt particles. In this way, the large particle size of the lithium iron phosphate salt particles of the embodiment of the present application is better achieved, and excellent kinetic performance is achieved when it is used as a positive electrode material.
[0131] In any embodiment, after the first sintering and before the second sintering, the product after the first sintering is carbon-coated. Based on the total weight of the product after the first sintering, the amount of carbon coating is 0.01 weight%-1.99 weight%, and can be optionally 0.2 weight%-1.6 weight%, specifically 0.2 weight%, 0.3 weight%, 0.4 weight%, 0.5 weight%, 0.6 weight%, 0.7 weight%, 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight% or 1.6 weight%, or a range between any two of the above values.
[0132] By coating the product after the first sintering with carbon within the above-mentioned content range after the first sintering and before the second sintering, a uniform and dense carbon coating layer can be formed on the surface of the lithium iron phosphate salt particles during the second sintering process, and each particle is coated.
[0133] In any embodiment, the carbon coating is performed by vapor deposition during sintering, or by carbonizing and coating the carbon source at high temperature.
[0134] In the preparation method of the lithium iron phosphate salt particles of the embodiment of the present invention, the implementation method of the carbon coating is not particularly limited, and the lithium iron phosphate salt particles can be optionally carbon-coated by a vapor deposition method, thereby forming a uniform and dense carbon coating layer on the surface of the lithium iron phosphate salt particles and coating each particle.
[0135] In any embodiment, after the first sintering and the second sintering, the sintered product is crushed, and the crushing can be selected from one or more of grinding, sand milling, mechanical crushing, and air flow crushing.
[0136] In the method for preparing the lithium iron phosphate salt particles according to the embodiment of the present invention, the pulverization method is not particularly limited. By adopting the above-mentioned specific pulverization method, it is advantageous to obtain the desired primary average particle size.
[0137] [Positive electrode]
[0138] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the lithium iron phosphate salt particles of the first aspect of the present application as a positive electrode material. The lithium iron phosphate salt particles of the present application have a large particle size when applied to a secondary battery, and also have excellent kinetic properties when used as a positive electrode material.
[0139] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, the battery aluminum foil of the present application is used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming the battery aluminum foil of the present application on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0140] In some embodiments, the positive electrode material may adopt a positive electrode material for a battery that is well known in the art. As an example, the positive electrode material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode materials for batteries may also be used. These positive electrode materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0141] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0142] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0143] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0144] [Negative electrode]
[0145] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0146] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0147] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0148] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0149] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0150] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0151] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0152] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0153] [Electrolytes]
[0154] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0155] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0156] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0157] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0158] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0159] [Isolation film]
[0160] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0161] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0162] [Secondary battery]
[0163] In one embodiment of the present application, a secondary battery is provided, which includes the positive electrode plate.
[0164] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0165] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0166] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0167] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0168] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.
[0169] In some embodiments, reference Figure 6 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0170] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0171] Figure 7 4 is an example of a battery module. Figure 7 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0172] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0173] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0174] Figure 8 and Fig. 9 1 is a battery pack 1 as an example. Figure 8 and Fig. 9 The battery pack 1 may include a battery box and a plurality of battery modules 6 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0175] [Electrical devices]
[0176] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0177] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0178] Fig.10 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0179] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0180] Example
[0181] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0182] Example 1
[0183] 1. Preparation of lithium iron phosphate particles
[0184] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratios of Li element, Fe element and P element are such that Fe:P=0.968:1, Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose added is such that after the first sintering is completed, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.
[0185] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 0.40μm, and spray dry it (the negative pressure of the high-speed spray dryer is -650~-200Pa, the inlet temperature is 300℃~360℃, and the outlet temperature is 100℃~140℃). The dried reactants are loaded into a sintering furnace for the first sintering, and the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.
[0186] Add glucose as a carbon source and polyaniline as a carbon film-forming agent to the obtained powder, and then mix with water to obtain a material with a solid content of 40%. Among them, the amount of glucose and polyaniline added satisfies that the carbon content of the product after the second sintering is 1.2% (based on the total weight of the lithium iron phosphate salt particles), and the weight ratio of glucose to polyaniline satisfies glucose: polyaniline = 1:2. The above materials are processed by ball milling and sand milling to obtain a slurry, and the Dv50 of the insoluble matter in the slurry is 550nm. Spray drying (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for a second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870 nm. After demagnetization, lithium iron phosphate salt particles are obtained, with a carbon content of 1.2% and a Ti content of 5000 ppm in the lithium iron phosphate salt particles.
[0187] The obtained lithium iron phosphate particles were observed under SEM (scanning electron microscope), and the results were as follows Figure 1 of Figure 1 The obtained lithium iron phosphate particles were observed under TEM (transmission electron microscope), and the results were as follows Figure 1 b and Figure 1 As shown in c.
[0188] 2. Preparation of positive electrode
[0189] 2.0 wt% polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone (NMP), and then 1.0 wt% Super P, 0.5 wt% carbon nanotubes and 96.5 wt% of the above positive electrode materials were added and stirred and mixed to obtain positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil, and then transferred to a vacuum drying oven for complete drying. The dried pole piece was rolled and punched to obtain a positive electrode piece.
[0190] 3. Preparation of negative electrode sheet
[0191] Active material artificial graphite, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC Na) are dissolved in solvent deionized water at a weight ratio of 96.7:1.3:0.8:1.2, and mixed evenly to prepare negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0192] 4. Preparation of electrolyte
[0193] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3:7, and LiPF6 lithium salt was dissolved in the organic solvent to prepare a solution with a weight content of 12.5% to obtain an electrolyte.
[0194] 5. Isolation film
[0195] Polypropylene film is used as the isolation film.
[0196] 6. Preparation of lithium-ion batteries
[0197] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium-ion battery of Example 1.
[0198] The lithium ion battery obtained in Example 1 was subjected to the performance test described below, and the results are shown in 1.
[0199] Example 2
[0200] The same procedure as in Example 1 was followed except that the Dv50 particle size of the particles crushed after the first sintering was controlled to be 350 nm, thereby obtaining lithium iron phosphate particles having a primary average particle size of 500 nm.
[0201] Example 3
[0202] The same procedure as in Example 1 was followed except that the Dv50 particle size of the particles pulverized after the first sintering was controlled to be 1200 nm, thereby obtaining lithium iron phosphate particles having a primary average particle size of 3000 nm.
[0203] Example 4
[0204] The same procedure as in Example 1 was carried out except that the temperatures of the first sintering and the second sintering were changed to 620° C. and 740° C., respectively, and the Ti content of the product was controlled to 2500 ppm.
[0205] Example 5
[0206] The same procedure as in Example 1 was carried out except that the temperatures of the first sintering and the second sintering were changed to 655° C. and 755° C., respectively, and the Ti content was adjusted to 6000 ppm.
[0207] Example 6
[0208] The same procedure as in Example 1 was carried out except that the modifying element was replaced by V from Ti.
[0209] Example 7
[0210] The same procedure as in Example 1 was carried out except that the modifying element was replaced by Nb from Ti.
[0211] Example 8
[0212] The average particle size of lithium iron phosphate particles is 920nm and the BET specific surface area is 3.0m 2 / g, and the carbon content was 0.8 wt %, the same procedure as in Example 1 was carried out.
[0213] Example 9
[0214] The average particle size of lithium iron phosphate particles is 790nm and the BET specific surface area is 8.0m 2 / g, and the carbon content was 1.4 wt %, the same procedure as in Example 1 was carried out.
[0215] Example 10
[0216] The carbon content after the first sintering was adjusted to 0.05 wt %, and the primary average particle size of the product was adjusted to 1250 nm and the BET specific surface area was adjusted to 6.0 m 2 / g, and the carbon content was 1.2% by weight, the same procedure as in Example 1 was carried out.
[0217] Embodiment 11
[0218] The average particle size of lithium iron phosphate particles is 520nm and the BET specific surface area is 6.8m 2 / g, and the carbon content after the first sintering was adjusted to 0.4 wt %. The same procedure as in Example 1 was carried out.
[0219] Example 12
[0220] The BET specific surface area of the regulated product is 7.2 m 2 / g, and the carbon content was 1.6 wt %, the same procedure as in Example 1 was carried out.
[0221] Embodiment 13
[0222] The BET specific surface area of the regulated product is 7.8 m 2 / g, and the carbon content was 2 weight %, the same procedure as in Example 1 was carried out.
[0223] Embodiment 14
[0224] The temperature of the first sintering was controlled at 620°C, and the temperature of the second sintering was controlled at 730°C. The weight ratio of glucose to polyaniline satisfied glucose:polyaniline=1:4. The BET specific surface area of the lithium iron phosphate particles was 3.0 m 2 / g, and the carbon content was 2 weight %, the same procedure as in Example 1 was carried out.
[0225] Embodiment 15
[0226] The BET specific surface area of lithium iron phosphate particles is regulated to 8.0 m 2 / g, and the carbon content was 0.94% by weight, the same procedure as in Example 1 was carried out.
[0227] Example 16
[0228] The same procedure as in Example 1 was followed except that the primary average particle size of the lithium iron phosphate salt particles was adjusted to 650 nm and the Dv50 after the first sintering was adjusted to 450 nm.
[0229] Embodiment 17
[0230] The average particle size of lithium iron phosphate particles is 2500nm and the BET specific surface area is 5.5m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0231] Comparative Example 1
[0232] The BET specific surface area of lithium iron phosphate particles is regulated to 2.4 m 2 / g, and the carbon content was 0.7 wt %, the same procedure as in Example 1 was carried out.
[0233] Comparative Example 2
[0234] The carbon content was adjusted to 1.7% by weight, so that the BET specific surface area of the product was 12 m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0235] Comparative Example 3
[0236] The temperature of the second sintering was adjusted to 830 °C, and the BET specific surface area of the product was adjusted to 9.5 m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0237] Comparative Example 4
[0238] The average particle size of the product is 5000nm and the BET specific surface area is 4m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0239] Comparative Example 5
[0240] During the preparation process, one sintering was used and the BET specific surface area of the product was adjusted to 12 m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0241] Comparative Example 6
[0242] The temperature of the first sintering was adjusted to 760°C, the average particle size of the product was adjusted to 3200 nm, and the BET specific surface area was adjusted to 4.8 m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0243] Comparative Example 7
[0244] The carbon content of the product after the first sintering was controlled to be 1.1 wt %, and the primary average particle size of the product was regulated to be 300 nm, and the BET specific surface area was regulated to be 13 m 2 / g, the same procedure as in Example 1 was carried out except for this.
[0245] Comparative Example 8
[0246] The preparation process was carried out in the same manner as Example 1 except that no carbon film-forming agent was used, the temperature of the first sintering was controlled at 600°C, the temperature of the second sintering was controlled at 720°C, and the carbon content of the product was controlled to 0.5%.
[0247] 1. Determination of relevant parameters of lithium iron phosphate particles
[0248] 1. Primary average particle size
[0249] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Among them, the "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points through the edge. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 80nm and the primary particle size of lithium iron phosphate salt particles with a primary particle size greater than 80nm can be counted in the electron microscope scanning photo, and the primary average particle size of the lithium iron phosphate salt particles = the primary particle size of the total lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. Among them, in the above-mentioned particle size statistical process, particles with a primary average particle size less than or equal to 80nm are not included in the statistical range.
[0250] 2. BET specific surface area
[0251] The specific surface area was tested by gas adsorption method according to the GB / T19587-2017 test standard, as follows: lithium iron phosphate granular salt was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the material.
[0252] 3. Dv50
[0253] Referring to GB / T19077.1-2016, the Dv50 value of the lithium iron phosphate salt particles was measured using a laser particle size analyzer (Malvern Master Size 3000). In addition, the Dv10, Dv90, and Dv99 of the present application were also measured in the same manner.
[0254] 4. Carbon content
[0255] The lithium iron phosphate particles are burned in a high-frequency induction furnace and then the carbon content is tested by infrared absorption method. The specific testing process is based on the standard GB / T 20123-2006 / ISO 15350:2000.
[0256] 5. Morphology test
[0257] The embodiment 10 and the existing lithium iron phosphate positive electrode material were tested by ZEISS sigma 300 scanning electron microscope, and then tested according to the standard JY / T010-1996, and the sample morphology was observed. The observation results are shown in Figure 2 a, b.
[0258] 2. Determination of battery performance
[0259] 1. Battery capacity in grams
[0260] 2.0000g of sample was mixed with 0.1111g of conductive carbon black and 0.1111g of PVDF (by mass ratio of 0.9:0.05:0.05), and then 2.5g of organic solvent NMP (N-methylpyrrolidone) was added. After being fully mixed, it was coated on aluminum foil into a film with a thickness of 140 microns, vacuum dried at 120℃ for 2h, punched into 13mm discs using a puncher, and pressed into discs using a tablet press at 10Mpa, and kept in vacuum at 120℃ for 12h. The weight of the positive electrode sheet was weighed, and the loading amount of active material was 11-12mg. A button cell was assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a mixed solvent of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) in a volume ratio of 1:1, an electrolyte of LiPF6, and a diaphragm of Celgard2400 microporous polyethylene film. The assembled battery was tested for electrical performance on a blue electric tester. In the voltage range of 2.0V to 3.75V, charge / discharge twice at 0.1C constant current, then charge / discharge twice at 1C constant current, and test the specific capacity. There is a constant voltage process during the charging process, the constant voltage is 3.75V, and the constant voltage cut-off current is 50μA. The gram capacity is the discharge capacity under the first 0.1C cycle.
[0261] 2. Battery capacity ratio when discharged from 1C to 3.2V (η value)
[0262] The preparation and testing process of the battery is as follows: 2.0000g of sample is mixed with 0.1111g of conductive carbon black and 0.1111g of PVDF (by mass ratio of 0.9:0.05:0.05), and then 2.5g of organic solvent NMP (N-methylpyrrolidone) is added, and after being fully mixed, a film with a thickness of 140 microns is coated on aluminum foil, vacuum dried at 120°C for 2h, and a round piece with a diameter of 13mm is punched using a puncher, and a sheet press is used to press the sheet at 10Mpa, and the vacuum insulation at 120°C is carried out for 12h, and the weight of the positive electrode sheet is weighed, wherein the loading amount of the active material is 11-12mg. A button cell is assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a mixed solvent of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) in a volume ratio of 1:1, an electrolyte LiPF6, and a diaphragm of Celgard2400 microporous polyethylene film. The assembled battery was tested on a blue battery tester for electrical performance. Within the voltage range of 2.0V to 3.75V, the battery was charged / discharged at 0.1C constant current for two weeks, and then charged / discharged at 1C constant current for two weeks to test the specific capacity. There was a constant voltage process during the charging process, with a constant voltage of 3.75V and a constant voltage cut-off current of 50μA.
[0263] The capacity value extracted when the discharge voltage is 3.2V is recorded as C1, and the capacity value extracted when the discharge voltage is 2.0V is recorded as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, the constant voltage is 3.75V, and the constant voltage cut-off current is 50μA.
[0264] 3. Slurry solid content
[0265] Prepare an electronic balance (accuracy 0.0001), an oven, and a glass drying tray. Take 8-10g of the positive electrode slurry sample and spread it evenly on the sample tray, and record the mass of the slurry before drying as A. Cover the oven door and heat it. As the heating progresses, the temperature in the furnace continues to rise, rising to 130°C for 5 hours. After drying, cool it in the oven and take it out, record the mass of the slurry after drying, perform multiple drying, and record the mass after drying as B after the sample mass is constant. Slurry solid content = (A / B) × 100%.
[0266] 4. Magnetic material content
[0267] 1) Weigh 1 kg of sample and put it into a plastic bucket. Add 6 L of deionized water. Use a plastic tube to cover a magnetic bar with a diameter of 24 mm and a length of 240 mm (magnetic field strength of 6000 Gauss). Then use a heat-sealing clip to heat-seal the magnetic bar. Put the magnetic bar into the plastic bucket and seal it together. Stir at a speed of 60 rpm for 15 minutes.
[0268] 2) Prepare another clean bucket, add 5±0.2L of deionized water into the bucket, flush the magnetic material on the plastic tube into the solvent, reseal the magnetic rod, and repeat the above steps twice to ensure the accuracy of the amount of magnetic material extracted;
[0269] 3) Prepare a clean 1L beaker, rinse all the magnetic substances on the plastic tube into the beaker, use a magnetic block to suck the bottom of the beaker, and rinse 1-2 times;
[0270] 4) Use a measuring cylinder to measure 10 mL of deionized water and add it to a 100 mL beaker. Then measure 10 mL of 36%-38% hydrochloric acid and slowly add it to the beaker. Pour the prepared hydrochloric acid solution into the beaker, seal it and place it in an ultrasonicator for 2 minutes;
[0271] 5) After the ultrasonic treatment is completed, take out the beaker and use a magnetic block at the bottom of the beaker to absorb and gather the magnetic material, and pour the acid solution in the beaker into the waste liquid bucket; rinse the magnetic material in the beaker 3 times, and inject an appropriate amount of deionized water for filtration.
[0272] 6) Use a filter membrane with a pore size of 0.45 microns. After filtration, place the filter paper with magnetic particles on the surface on the slide of the cleanliness microscope and put it in an oven to dry at 60°C for (10±2) minutes. After drying, weigh the filter membrane and calculate the content of magnetic substances.
[0273] The higher the content of magnetic substances, the more serious the self-discharge of the battery cell is and the shorter the battery life is.
[0274] 5. Determination of kinetic properties
[0275] The kinetic performance of the battery in this application is specifically reflected in the measurement of the DC internal resistance (power performance).
[0276] 25℃ power performance test:
[0277] Capacity calibration: After the lithium ion batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, they were charged to 3.65V at a constant current of 0.33C, and then charged to 0.05C at a constant voltage of 3.65V. After the charging was completed, the tested batteries were kept at 25°C for 2 hours, and then discharged to 2.5V at a direct current of 0.33C, and the discharge capacity at room temperature was recorded as C0;
[0278] Adjust SOC (battery state of charge): After keeping the calibrated lithium-ion battery at 25°C for 2 hours, discharge it at a 1 / 3C0 discharge rate for 144 minutes to adjust the lithium-ion battery capacity to 10% SOC;
[0279] Power test: After the 10% SOC lithium-ion battery is left to stand at 25°C for 2h, it is discharged at a discharge rate of 3C0 for 30s under a pulse current I. The voltage before 3C0 discharge is recorded as V1, and the voltage at the end of 30s discharge is recorded as V2. The value of the DC internal resistance (V1-V2) / I is calculated. This data can be used to characterize the power performance of the battery.
[0280] 3. Parameters and performance in the embodiments and comparative examples
[0281] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured, as shown in Table 1.
[0282] Table 1
[0283]
[0284] According to the contents of Table 1, the primary average particle size, BET specific surface area and carbon content of the lithium iron phosphate salt particles obtained in Examples 1-17 of the present application all meet the requirements of the present application. As a result, their η values are all greater than or equal to 88%, indicating that the battery has a strong discharge power performance. When the battery is discharged to a low SOC (battery state of charge), it can still maintain a good power performance, that is, when the battery is discharged at a low current, the voltage drop of the battery is small. In addition, the dynamic performance values of the lithium iron phosphate salt particles in the embodiment are low, indicating that the mechanical properties of the battery are excellent. The lithium iron phosphate salt particles have a high gram capacity, a high solid content of the slurry and a low content of magnetic substances, indicating that the energy density and life characteristics of the battery are excellent.
[0285] In addition, according to Table 1, it can be seen that in Comparative Examples 1-8, whether by changing the parameter characteristics of the lithium iron phosphate salt particles themselves or changing the parameter characteristics in their preparation process, the resulting lithium iron phosphate salt particles do not meet the limitations of the present application, and at least one of the size characteristics, dynamic properties, gram capacity, solid content of the slurry or magnetic material content of the resulting lithium iron phosphate salt particles is significantly reduced, which obviously cannot meet the requirements of the present application.
[0286] It should be noted that the present application is not limited to the embodiments described. The embodiments described are only examples, and the embodiments having substantially the same structure as the technical idea and exerting the same effects within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, other methods of applying various modifications that can be thought of by those skilled in the art to the embodiments and combining some of the constituent elements in the embodiments to construct the embodiments are also included in the scope of the present application.
Claims
1. A lithium iron phosphate salt particle, characterized in that: The lithium iron phosphate particles have a primary average particle size of 500 nm to 3000 nm and a BET specific surface area of 3 m 2 / g~8m 2 / g, Calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is Cx weight %, wherein 0.8≤Cx≤2.
0.
2. The lithium iron phosphate salt particles according to claim 1, characterized in that: The primary average particle size of the lithium iron phosphate particles is 650nm to 2500nm; and / or, The BET specific surface area of the lithium iron phosphate particles is 4 m 2 / g~7m 2 / g; and / or, Calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is Cx weight %, wherein 1.0≤Cx≤1.
6.
3. The lithium iron phosphate salt particles according to claim 1 or 2, characterized in that: The lithium iron phosphate salt particles have a molecular formula of Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.
1.
4. The lithium iron phosphate salt particles according to claim 3, characterized in that: The Q comprises at least one of Ti, V, Mg and Nb, Calculated based on the total weight of the lithium iron phosphate particles, the content of Ti, V, Mg, and / or Nb is 1000ppm-10000ppm.
5. The lithium iron phosphate salt particles according to any one of claims 1 to 4, characterized in that: The lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles.
6. The lithium iron phosphate salt particles according to any one of claims 1 to 5, characterized in that: The capacity proportion of the lithium iron phosphate salt particles is η≥88%, and the definition of η is: a battery containing the lithium iron phosphate salt particles as a positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value extracted when the discharge voltage is 3.2V is recorded as C1, and the capacity value extracted when the discharge voltage is 2.0V is recorded as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
7. The lithium iron phosphate salt particles according to any one of claims 1 to 6, characterized in that: The lithium iron phosphate salt particles meet at least one of a) to f): a) the Dv10 of the lithium iron phosphate particles is ≥ 0.2 μm; b) the Dv50 of the lithium iron phosphate particles is 0.5-5 μm; c) the Dv90 of the lithium iron phosphate salt particles is ≤10 μm; d) the Dv99 of the lithium iron phosphate particles is ≤12 μm; e) The powder compaction density of the lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ; f) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
8. A method for preparing lithium iron phosphate particles, characterized in that: include: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein: The temperature of the first sintering is 500° C.-760° C., and the carbon content of the material after the first sintering is 0.01 wt %-0.79 wt %; The temperature of the second sintering is 700° C.-800° C., and the carbon content of the material after the second sintering is 0.8 wt %-2.0 wt %.
9. The method for preparing lithium iron phosphate salt particles according to claim 8, characterized in that: The lithium iron phosphate salt particles contain at least one of Ti, V, Mg, and / or Nb elements, and the content of the element is 1000ppm-10000ppm based on the total weight of the lithium iron phosphate salt particles.
10. The method for preparing lithium iron phosphate salt particles according to claim 8 or 9, characterized in that: The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein: The Dv50 of the product after the first crushing is 300nm-1200nm; The Dv50 of the product after the second pulverization is 500nm-5000nm.
11. The method for preparing lithium iron phosphate particles according to any one of claims 8 to 10, characterized in that: include: A raw material containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent and a modifier is provided, wherein the mixing ratio of the lithium source, the iron source and the phosphorus source, calculated on the basis of the atomic molar number of each element, satisfies Fe:P=0.96-0.985, Li:Fe=1.0-1.1:0.95-1.1; and the carbon source and the carbon film-forming agent, calculated on the basis of the weight ratio, satisfies carbon source:carbon film-forming agent=9:1-2:
8.
12. The method for preparing lithium iron phosphate salt particles according to any one of claims 8 to 11, characterized in that: The lithium source is a lithium compound, including one or more of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide and lithium acetate; The iron source is an iron compound, including at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric oxyhydroxide; The phosphorus source is a phosphoric acid compound, including one or more of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; The modifier includes at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, niobium pentoxide, niobium oxalate, niobium ethoxide, magnesium hydroxide, magnesium nitrate, and ammonium metavanadate; The carbon source includes at least one of citric acid, glucose, sucrose, starch, fructose and lactose; The carbon film-forming agent includes one or a combination of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone and polyvinyl alcohol.
13. The method for preparing lithium iron phosphate salt particles according to any one of claims 8 to 12, characterized in that: The heating rates in the first sintering and the second sintering are independently 2°C / min-20°C / min; the constant temperature time of the first sintering is 1h-6h; and the constant temperature time of the second sintering is 2h-12h.
14. The method for preparing lithium iron phosphate salt particles according to claims 8 to 13, characterized in that: In the second sintering, the product after the first sintering is carbon coated, and the amount of the carbon coating is 0.01 wt %-1.99 wt % based on the total weight of the product after the first sintering.
15. The method for preparing lithium iron phosphate salt particles according to claim 14, characterized in that: The carbon coating is performed by vapor deposition during the sintering process, or by carbonizing and coating the carbon source at high temperature.
16. The method for preparing lithium iron phosphate salt particles according to any one of claims 10 to 15, characterized in that: The pulverization can be selected from one or more of grinding, sand milling, mechanical crushing, and air flow crushing.
17. A positive electrode plate, characterized in that: The lithium iron phosphate salt particles according to any one of claims 1 to 7 or the lithium iron phosphate salt particles prepared by the preparation method of the lithium iron phosphate salt particles according to any one of claims 8 to 16 are used as positive electrode materials.
18. A secondary battery, characterized in that: Contains the positive electrode sheet as described in claim 17.
19. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 18.
Citation Information
Patent Citations
Method for preparing high-density lithium ferric phosphate
CN102009970A
Carbon-coated lithium manganese iron phosphate composite material and preparation method thereof
CN114620703A
Lithium iron phosphate precursor, lithium iron phosphate material and preparation method and application thereof
CN117133913A
Lithium-ion secondary-battery positive electrode material and manufacturing method therefor
WO2011129224A1